2015
DOI: 10.1159/000435855
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Children with Congenital Adrenal Hyperplasia

Abstract: Background/Aims: Factors in congenital adrenal hyperplasia (CAH) that may affect quality of life (QOL) include the need for lifelong medication, the risk of adrenal crisis, and hyperandrogenic symptoms. The objectives were to evaluate health-related QOL (HRQOL) in children with CAH, and whether CAH poses an additional burden compared to other endocrine disorders. Methods: The validated PedsQL 4.0 generic core scales were administered to subjects (8-18 years) with CAH and hypothyroidism and their parents. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
(36 reference statements)
4
14
2
1
Order By: Relevance
“…In contrast to the two previous reports [ 3 , 4 ], our pediatric participants with CAH did not report lower overall PedsQL™ Generic scores than healthy norms. In fact, they scored significantly higher on the physical health subscale.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the two previous reports [ 3 , 4 ], our pediatric participants with CAH did not report lower overall PedsQL™ Generic scores than healthy norms. In fact, they scored significantly higher on the physical health subscale.…”
Section: Discussioncontrasting
confidence: 99%
“…HRQL questionnaires are short, validated screening tools that are particularly useful when treating children with chronic conditions, such as CAH, to understand how the disease and therapy impact physical, emotional, and social functioning [ 13 ]. There are only two previous studies that examined QoL in children with CAH using validated HRQL screening tools [ 3 , 4 ]. However, these studies did not examine the relationship between QoL scores and hydrocortisone dosing or chronic androgen exposure, as measured by bone age Z-scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a Finnish study [ 69 ], including men and women with CAH, showed a better health-related QoL than the general Finnish population. Yau et al [ 66 ] found no differences in overall or specific health-related QoL between males and females, but again results were not presented separately. Halper et al [ 65 ] did not find any differences in QoL scores between sex and CAH subtypes.…”
Section: Discussionmentioning
confidence: 92%
“…The authors assume it might be explained by the children being on hydrocortisone, which has been found to have a less negative impact on QoL in adults than other glucocorticoids [ 67 ]. Yau et al [ 66 ] recruited 33 parents and their children with CAH, who also completed measures of QoL (PedsQL 4.0 generic core scales). Scores were compared to children with hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%